Predictive Analytics for Oil and Gas Asset Maintenance Using XGBoost Algorithm - Aziz, N.; Abdullah, M.H.A.; Osman, N.A.; Musa, M.N.; Akhir, E.A.P. (2023)
One of the most important aspects of the oil and gas industry is asset management at their respective platforms. Without proper asset management, it will lead to various unexpected scenarios including an increase in plant deterioration, increased chances of accidents and injuries, and breakdown of assets at unexpected times which will lead to poor and hurried maintenance. Given the significant economic contribution of the oil and gas sector to oil-producing countries like Malaysia, accurate asset maintenance prediction is essential to ensure that the oil and gas platform can manage its operations profitably. This research identifies the parameters affecting the asset failure on oil and platform that will be interpreted using the XGBoost gradient boosting model from machine learning libraries. The model is used to predict the assetâs lifetime based on readings collected from the sensors of each machine. From result, our prediction method using XGBoost for asset maintenance has presented a 6.43 increase in classification accuracy as compared to the Random Forest algorithm. Â© 2023, The Author(s), under exclusive license to Springer Nature Switzerland AG.